Enantioselective Michael Addition of 1,3-Diketones to Arenesulfonylalkylindoles: A Flexible Gateway to Optically Active 3-sec-Alkyl-Substituted Indoles Containing a Pyrazole Skeleton - Zuo, Zongle; Zhang, Shilu; Wang, Rongming; He, Wujun; Wu, Song; Xie, Xiaohua; Qin, Dabin; Jing, Linhai (Synthesis, 2013)
Enantioselective Michael addition of 1,3-diketones to alkylideneindolenines generated in situ from arenesulfonylalkylindoles is described, and a series of optically active C3-alkyl-substituted indole derivatives has been obtained. The resulting adducts can be readily converted into 3-sec-alkyl-substituted indoles containing a pyrazole skeleton, with direct connection between the α- and 4-positions, without decrease of the enantioselectivity.
Keywords: asymmetric catalysis; Michael addition; arenesulfonylalkylindoles; 1,3-diketones; pyrazoles